Passionate Digital Play-Based Learning. (Re)Learning in computer games like Shadow of the Colossus - Mitgutsch, Konstantin (Eludamos: Journal for Computer Game Culture, 2009)
Abstract: In the last decades the potentials for teaching and learning based on computer games have increasingly become a focus in scientific research and the computer industry. It is argued that computer games are a valuable tool to enrich learning. While in traditional educational institutions the enhancement of motivation for learning something was often reduced to a pressure to perform for someone, games are said to lead to a more learner-centred teaching. However the “great expectations” were not fulfilled: The reasonable symbiosis of meaningful content and an engaging environment transformed through digital media stayed beyond its instructional expectations. Especially the dimension of passion as a circular and non-linear process of relearning and learning anew was overlooked in a majority of theories, concepts and designs of games. In this understanding the passionate dimension of learning refers to a kind of learning, where the learners’ expectations disprove and he explores resistive experienced. The paper outlines how a unique game such as "Shadow of the Colossus" can open up a new horizon of experiences that lead to a passionate dimension of learning by playing digital games. By stressing a theoretical learning perspective on the process of experience within the game "Shadow of the Colossus", a new understanding of learning based on playing games will be given. Therefore the paper will give insight into the concept of learning by passion and Digital Play-Based Learning and show a new dimension for twenty-first century learning games.